Allergic Broncho Pulmonary Aspergillosis Complicated by Nocardiosis. (25th December 2012) - Sharma, Brijesh; Ghosh, Gopal; Kamble, Ulka; Chaudhary, Karan; Chauhan, Ajay; Lamba, B. M. S.; Chowdhary, Anuradha; Gupta, B. B.
Abstract : We describe a 70-year-old male with a history of diabetes mellitus, hypertension, and asthma who presented with increasing breathlessness for 5 months. He was diagnosed to have allergic bronchopulmonary aspergillosis (ABPA) by serological and radiographic criteria. He was treated with steroids and itraconazole. After initial improvement, he developed fever with cough and mucopurulent sputum. X-ray chest revealed multiple cavities with air fluid level. Patient was treated with antibiotics without any response. Sputum was negative for acid fast bacilli (AFB). Sputum culture for bacteria and fungus did not reveal any significant growth; however a delayed growth of Nocardia was noted on fungal plates. Modified Ziehl Nelsen stain was positive for AFB. Patient was treated with cotrimoxazole. We discuss the serological and radiological criteria of ABPA, presentation and treatment of nocardia pulmonary infection and other possible causes of necrotizing pneumonia in immunocompromised settings.